2017
DOI: 10.1002/clc.22818
|View full text |Cite
|
Sign up to set email alerts
|

Isometric handgrip echocardiography: A noninvasive stress test to assess left ventricular diastolic function

Abstract: Background Cycle exercise echocardiography is a useful tool to “unmask” diastolic dysfunction; however, this approach can be limited by respiratory and movement artifacts. Isometric handgrip avoids these issues while reproducibly increasing afterload and myocardial oxygen demand. Hypothesis Isometric handgrip echocardiography (IHE) can differentiate normal from abnormal diastolic function. Methods First recruited 19 young healthy individuals (mean age, 24 ± 4 years) to establish the “normal” response. To exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Handgrip exercise (HG) is a simple bedside maneuver to increase the intensity of murmur of mitral regurgitation (MR) during auscultation [ 1 ]. In addition, HG has been used in echocardiography as a means of stress test to identify exertion induced ischemia or exertion induced left ventricular diastolic dysfunction [ 2 , 3 ]. Furthermore, HG has been used in combination with dobutamine stress echocardiography to identify patients with MR who would probably benefit from percutaneous mitral valve repair [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Handgrip exercise (HG) is a simple bedside maneuver to increase the intensity of murmur of mitral regurgitation (MR) during auscultation [ 1 ]. In addition, HG has been used in echocardiography as a means of stress test to identify exertion induced ischemia or exertion induced left ventricular diastolic dysfunction [ 2 , 3 ]. Furthermore, HG has been used in combination with dobutamine stress echocardiography to identify patients with MR who would probably benefit from percutaneous mitral valve repair [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study on stress echocardiography showed that left ventricular (LV) diastolic dysfunction clearly appeared during IHG in hypertensive patients compared with healthy subjects 12 . Another study reported that E/E′, which was correlated with LV filling pressure, changed minimally during IHG in healthy young subjects, whereas E/E′ increased more dramatically in elderly subjects 13 . One possible explanation for the different results in healthy young and elderly hypertensive subjects may be that diastolic dysfunction during IHG is associated with relative myocardial ischemia caused by increases in LV afterload and myocardial oxygen demand.…”
Section: Discussionmentioning
confidence: 99%
“…Both bicycle (preferably supine) and treadmill exercise protocols are useful for this purpose [15]. Passive leg lifting and isometric exercise with handgrip may be potential alternatives to dynamic exertion, but need to be more extensively validated to be recommended for clinical use [29][30][31].…”
Section: Echocardiographic Evaluation Of LV Filling Pressurementioning
confidence: 99%